REMOVAL OF FLUORIDE FROM WATER USING EGGSHELLS - JAYALLAN, YUWARAAJ (IRC, 2017)
Fluoride is an abundant element of the world. Fluoride intake by human occurs through food consumption and drinking water. Fluoride content in human beyond a threshold point (1.5 mg/L in water as set by the World Health Organization (WHO)) can cause detrimental health effect to the human body. Hence removing fluoride from water has become a necessity. Many study has been conducted in these area, producing technologies and techniques such as reverse osmosis, electrodialysis and adsorption. Adsorption is a prominent area of study with many materials being investigated for their properties as a useful adsorbent. This study investigates eggshell as the adsorbent for removal of fluoride from water. The variables studied are contact time, adsorbent dosage, initial concentration of fluoride, agitation speed and temperature. Eggshell powder were prepared in a laboratory, and heated using an oven at 110 °C. The fluoride concentrated water were introduced to a Erlenmeyer flask and fluoride removal efficiency were tabulated for various parameters, contact time (15-80 mins), initial concentration (5-20 mg/L), adsorbent dosage (0.3-0.6g), agitation speed (100-250 rpm) and temperature (25-40°C). The best Fluoride removal adsorption rate of 72.25% was obtained for 0.6g of adsorbent dosage, 4 mg/L of fluoride concentration at 250 rpm and 25°C with a contact time of 100 minutes. The study also showed Langmuir and Freundlich adsorption isotherm model for removal of fluoride from water.